2000
DOI: 10.1016/s0022-5347(05)67139-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety and Patient Acceptance of Sildenafil Citrate as Treatment for Erectile Dysfunction

Abstract: Sildenafil citrate is effective oral first line treatment for erectile dysfunction. Although more than 50% of men reported adverse effects, most were considered mild and rarely resulted in treatment cessation. There was a trend in those on intracavernous injection who responded to sildenafil to continue intracavernous injection as the only therapy or as an alternative to sildenafil. Also, we noted that some cases refractory to sildenafil responded to intracavernous injection. These findings imply that intracav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
69
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 18 publications
9
69
1
Order By: Relevance
“…It appears to be effective for symptomatic relief of ED in a wide variety of men. 5 However, not all men suffering from ED have effectively responded to sildenafil. 6 Early treatment discontinuation rates for the drug attributed to the patients' dissatisfaction range from 14% to as high as 47%.…”
Section: Introductionmentioning
confidence: 99%
“…It appears to be effective for symptomatic relief of ED in a wide variety of men. 5 However, not all men suffering from ED have effectively responded to sildenafil. 6 Early treatment discontinuation rates for the drug attributed to the patients' dissatisfaction range from 14% to as high as 47%.…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts significantly to that reported previously (2.6% and 9%). 6,11 This is, however, less than the reported alprostadil ICI drop-out rate of 37%. 21 As such, the role of high dose salvage therapy is limited by patient acceptance of a higher incidence of adverse effects.…”
Section: Discussionmentioning
confidence: 67%
“…10 McMahon et al reported a similar response rate of 67.5% but a higher incidence of adverse effects of 53.6%. 11 These authors report a similar efficacy rate but a higher incidence of adverse effects compared to that reported by the Sildenafil Study Group. 6 The maximum dose of sildenafil recommended by the manufacturer is 100 mg. A study was designed to prospectively review a group of patients with chronic ED, unresponsive to sildenafil 100 mg, who were treated in a home setting with doses of sildenafil in excess of the recommended maximum dose (150 mg and 200 mg).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…[5][6][7][8] Several authors have reported that 15-25% of men previously treated with intracavernous injection therapy who respond to sildenafil will choose to alternate between both forms of therapy according to circumstance. 9,10 Combination therapy using sildenafil and intracavernous combination pharmacotherapy have been reported to salvage 30% of men refractory to either treatment alone. 11 We report three cases of priapism occurring in men following intracavernous self-administration of vasoactive drugs following administration of a phosphodiesterase inhibitor drug.…”
Section: Introductionmentioning
confidence: 99%